Unraveling the linguistic features of Facebook comments amidst live press conferences - Chew, Shin Yi; Jiang, Jie Ting; Soh, Siak Bie (Journal of Modern Languages, 2024)
Over the years, online communication has become increasingly popular, evolving from purely text-based formats to multifaceted media. Since the outbreak of COVID-19, live streaming of press conferences and other events on social media has dramatically increased. However, there is a lack of studies investigating the linguistic features of netizens’ online communication during live streaming of public events. Therefore, this study aimed to analyse the linguistic features of Facebook comments posted by Malaysian netizens during COVID-19 live press conferences and explore the functions of these linguistic features. In this study, a total of 1339 comments were collected during the live streaming of COVID-19 press conferences by New Straits Times on Facebook. The collected data were analysed following Crystal’s (2006) list of netspeak features. The findings revealed that Malaysian netizens used abbreviations (21.9%), emojis (13.2%), stickers (5.5%), particles (5.2%), punctuation marks (3.6%), translanguaging (3.3%), capitalisation (1.8%), and repetitions of letters (1.6%) when commenting on the COVID-19 live press conferences. The functions of these linguistic features include time-saving, emotional emphasis, identity portrayal, and others.